Adaptation of Aura Colour Interface Content Presentation based on Learners Emotion in Personal eLearning Environment using Production Rules - Rahmah, Mokhtar; Fauziah, Zainuddin; Nor Azhar, Ahmad; Roslina, Abd. Hamid (UTM Academic Leadership (UTMLead), 2016)
Personalization is a suitable approach to adapt the learner to its learning environment.Adaptation for personalization is based on modality and affective aspects of the learner. Most research into adaptation is focusing on modality aspect, thus adaptation in affective aspect is crucial to be explored. This innovative prototype namely, EmoAPeL was developed to adapt the aura colour interface content presentation based on learner’s emotion in Personal e-Learning Environment using an intelligent production rule. EmoAPeL has been tested to 30 Universiti Malaysia Pahang students. The mean results show 88.5% of the students agreed that EmoAPeL motivates their inclusive learning environment. EmoAPeL development concept can be embedded to any eLearning systems.